HYDROGEN AS A DECARBONIZATION VECTOR: A SYSTEMATIC REVIEW OF ITS POTENTIAL FOR MITIGATING ENVIRONMENTAL POLLUTION IN INDUSTRIAL AND TRANSPORTATION SECTORS - muhibbudin, ismail; Mubarak, Sanni (Journal Of Renewable Energy Engineering, 2025)
The escalating global environmental crisis, largely driven by fossil fuel dependency, underscores the urgent need for sustainable alternatives. Hydrogen has emerged as a key candidate for achieving deep decarbonization in industrial and transportation sectors. This study systematically reviews 60 peer-reviewed publications from 2010–2024 to assess hydrogen’s environmental, technical, and socio-economic implications. The findings indicate that hydrogen, particularly when produced via renewable electrolysis, offers substantial emission reductions and strong synergy with fuel cell technologies, though infrastructure costs and storage challenges remain critical barriers. The paper concludes that a structured hydrogen economy could significantly enhance global sustainability, provided that supportive policies and investment frameworks are established.